Integration of tube end forming in wire arc additive manufacturing: An experimental and numerical investigation - Pragana, João (2021)
Integration of tube end forming operations in metal additive manufacturing routes has a great potential for the fabrication of customized features in additively deposited hollow parts. This paper is focused on the integration of tube expansion with rigid tapered conical mandrels to highlight the advantages in the construction of overhanging flares derived from the elimination of support structures and prevention of humping. The work draws from the mechanical and formability characterization of stainless steel AISI 316L tubes produced by wire arc additive manufacturing (WAAM) to the experimental and numerical simulation of the construction of over hanging flares by tube expansion. Strain loading paths obtained from digital image correlation and finite element analysis combined with the strain values at the onset of necking and fracture allow determining the critical ductile damage that additively deposited tubes can safely withstand. Results show that despite formability of additively deposited tubes being influenced by a dendritic based microstructure, their performance is adequate for tube end forming operations, such as tube expansion, to be successfully integrated in metal additive manufacturing without the need of using expensive hardware and complex deposition strategies.